2008
DOI: 10.1111/j.1462-5822.2007.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

ASK1-p38 MAPK-p47phox activation is essential for inflammatory responses during tuberculosis via TLR2-ROS signalling

Abstract: SummaryThe roles of intracellular reactive oxygen species (ROS) and related signalling pathways in mycobacterial infection are largely unknown. Here we show that tuberculin purified protein derivative (PPD)/Toll-like receptor (TLR) 2/ROS signalling through activation of apoptosis-regulating signal kinase (ASK) 1 and p47phox pathways is responsible for the induction of proinflammatory responses during tuberculosis (TB) infection. Tuberculin PPD stimulation resulted in rapid activation of mitogen-activated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 51 publications
8
105
1
Order By: Relevance
“…These data concur with our previous findings that tuberculin PPD-induced ROS production is dependent on TLR2 in monocytes/macrophages (13). In addition, our study shows that Mtb treatment triggered biphasic association of TLR2 and NOX2 at 1 min and 30 min (see Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data concur with our previous findings that tuberculin PPD-induced ROS production is dependent on TLR2 in monocytes/macrophages (13). In addition, our study shows that Mtb treatment triggered biphasic association of TLR2 and NOX2 at 1 min and 30 min (see Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we showed that a tuberculin PPD could inhibit the activation of inflammatory signaling by TLR2 in murine BMDMs and human primary monocytes (13). In the current study, we extended this observation to demonstrate that Mtb-mediated ROS production is largely dependent on NOX2 and TLR2.…”
Section: Mtb Induces Nox2-derived Ros Production In Macrophages Via Tlr2supporting
confidence: 73%
See 1 more Smart Citation
“…This results in the phosphorylation and activation of downstream p38 and JNK (49). We determined the activation state of ASK1 by Western blotting analysis.…”
Section: Figure 5 Activation Of Mapk Signaling Is Observed In Macropmentioning
confidence: 99%
“…One major source of ROS in macrophages is the phagocytic NADPH oxidase complex (NOX2), which consists of a membrane-bound fraction (gp91 phox and p22 phox ) and an array of cytoplasmic factors (p40 phox , p47 phox , p67 phox , and Rac) that translocate to the membrane resulting in formation of a primed and active NOX2 complex (4 -7). ROS production occurs following Fc␥R cross linking (8,9), during phagocytosis (2,10), and engagement of TLR4 or TLR2 (11)(12)(13). Superoxide radicals (O 2 . )…”
mentioning
confidence: 99%